(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purchase decision is assumed to be a student’s decision to choose, that is, a decision taken by a person about which brand to buy by choosing one of several available alternatives. The purpose of this study was to determine the effect of Celebrity Endorser and Institutional Image on Student Decisions in Choosing a Campus at the Universitas Hindu Indonesia in Denpasar. The number of samples is 89 respondents. The analysis technique used is regression analysis. (2) Institutional image partially has a significant positive effect on student decisions to choose. (3) simultaneous celebrity endorser and institutional image have a significant effect on student decisions to choose. The magnitude of the influence of Celebrity Endorser and Institutional Image on student decisions to choose is 48.5%. The suggestions that can be given by researchers are to maintain or add other artists to do Celebrity Endorsers, and to maintain and improve the Institutional Image to be able to attract more prospective students to study campus at the Universitas Hindu Indonesia in Denpasar.